(untitled) (Journal of actual problems of jurisprudence, 2021)
The article considers the method of extortion through the prism of the qualification of crimes within the forensic characteristics of crimes, since the question of the way of committing such a criminal offense as extortion is caused by the ambiguous treatment of extortion in the Criminal Code of the Republic of Kazakhstan. A comparison of the dispositions of articles adjacent to extortion is made. A criminal law analysis of the nature of the two main types of methods of extortion by organized criminal groups in the legal space of the Republic of Kazakhstan, in the practice of investigation, was conducted; the threat of disseminating information that disgraces the victim or his relatives, or other information, the announcement of which may cause significant harm to the interests of the victims him or his loved ones named us as “blackmail”. It is concluded that the requirements for the transfer of someone else’s property or the right to property or the commission of other actions of a property nature under the threat of dissemination of information that dishonors the victim or his relatives or other information whose disclosure can cause significant harm to the interests of the victim or his relatives and constitute the content Way of committing extortion by organized criminal groups. Key words: organized criminal groups, extortion, way of committing extortion, criminal offenses, forensic characteristics, demand for property transfer.